Impact of family history of breast cancer on tumour characteristics, treatment, risk of second cancer and survival among men with breast cancer (Swiss Medical Weekly, 2013)
BACKGROUND: Male breast cancer patients have a higher risk of developing a second primary cancer, but whether this risk differs according to the family history of breast or ovarian cancers remains to be elucidated. We aimed to determine the effect of a positive family history among men diagnosed with breast cancer on tumour characteristics, treatment, second cancer occurrence and overall survival. METHODS: We included 46 patients with known information on the family history of breast or ovarian cancer recorded at the Geneva Cancer Registry between 1970 and 2009. We compared patients with and without a family history with chi-square of heterogeneity, risk of second cancer with standardised incidence ratios (SIRs), and overall survival by Kaplan-Meier methods. RESULTS: Approximately 20% of men with breast cancer had a positive family history. No differences were observed between men with and without familial risk except that patients with increased risk were more likely to receive radiotherapy and hormone therapy when compared with patients without familial risk. This more complete therapy is likely to be explained by the heightened awareness of cancer treatment among breast cancer patients with affected family members. Six men developed a second cancer. SIRs for second cancer were not significantly increased among patients with or without familial risk (1.93, 95% confidence interval [CI] 0.23–6.97 and 1.04, 95% CI 0.28–2.66, respectively). Overall survival was not significantly different between the two groups. CONCLUSIONS: Prognosis was similar among patients with or without familial risk. Our results are however based on small numbers and larger registry-based cohorts of males with precise data on familial risk are still warranted.